2014
DOI: 10.1007/s11831-014-9107-y
|View full text |Cite
|
Sign up to set email alerts
|

Variational-Based Reduced-Order Model in Dynamic Substructuring of Coupled Structures Through a Dissipative Physical Interface: Recent Advances

Abstract: This paper deals with a variational-based reduced-order model in dynamic substructuring of two coupled structures through a physical dissipative flexible interface. We consider the linear elastodynamic of a dissipative structure composed of two main dissipative substructures perfectly connected through interfaces by a linking substructure. The linking substructure is flexible and is modeled in the context of the general linear viscoelasticity theory, yielding damping and stiffness operators depending on the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 71 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…The concept of entropy theory is an abstract notion of probability distribution, which can represent the probability of any research object. Therefore, dissipative structure theory and information entropy theory have been widely applied and extended to physical [32], chemical [33], biological [34], social [35], and economic [36] systems to describe the relationship between competition and cooperation amongst the elements of a system and the degree of disorder of a system or material movement.…”
Section: Dissipative Structure Theory and Entropy Theory In Rural Stumentioning
confidence: 99%
“…The concept of entropy theory is an abstract notion of probability distribution, which can represent the probability of any research object. Therefore, dissipative structure theory and information entropy theory have been widely applied and extended to physical [32], chemical [33], biological [34], social [35], and economic [36] systems to describe the relationship between competition and cooperation amongst the elements of a system and the degree of disorder of a system or material movement.…”
Section: Dissipative Structure Theory and Entropy Theory In Rural Stumentioning
confidence: 99%
“…Benfield and Hruda in 1971 [22] proposed a component mode substitution using the Craig-Bampton method for each appendage. Reviews concerning the substructuring techniques can be found in [55,61,125,143,154,157].…”
Section: Case Of Nonhomogeneous Uncertainties Taken Into Account By Umentioning
confidence: 99%
“…The substructuring techniques have deeply been studied [20,21,22]. As written in [23]: "historically, the concept of substructures was first introduced by Argyris and Kelsey in 1959 [24] and by Przemieniecki in 1963 [25] and was extended by Guyan and Irons [7,26]. Hurty [27,28] considered the case of two substructures coupled through a geometrical interface.…”
Section: Introductionmentioning
confidence: 99%